Spectral Study of Pt (II), Cr (II) Polymeric Complexes of the Ligand N- Crotonyl -2- Hydroxy-Phenylazomethine - Mahdi, Alyaa Esam (Al-Khwarizmi Engineering Journal, 2013)
The polymeric complexes were obtained from the reaction of polymeric Schiff base.N-crotonyl-2-hydroxyphenylazomethine (HL), with divalent metals Pt (II), Cr (II). The modes of bonding and overall geometry of the complexes were determine through spectroscopic methods and compared with that reported from analogous monomeric ligand. This study revealed square planer geometry around the metal center for [Pt(L)Cl] and distorted octahedral geometry for Cr complex [Cr(L)Cl(H2O)2].